A critical analysis of the obligation and liability of the carrier under the Rotterdam Rules - Ahmad, Muhamad Hassan; Masum, Ahmad; Nafees, Seeni Mohamed; Ali Mohamed, Ashgar Ali (LexisNexis, 2019)
At the international level, conventions on the contracts for the carriage of goods by sea were gradually developed and four major legal regimes have emerged, namely, the International Convention for the Unification of Certain Rules of Law relating to Bills of Lading 1924 (‘the Hague Rules’); the Hague Rules as Amended by the Brussels Protocol 1968 (‘the Hague-Visby Rules’); the United Nations Convention on the Carriage of Goods by Sea 1978 (‘the Hamburg Rules’); and the United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 (‘the Rotterdam Rules’). There were concerns over lack of uniformity among the previous legal regimes governing the international carriage of goods by sea, i.e., the Hague Rules, the Hague-Visby Rules and the Hamburg Rules. There was also no universal regime to govern contracts of carriage involving various modes of transport in connection with contracts of carriage by sea. In addition, they do not provide any legal basis for modern transport practices such as containerisation, the use of electronic transport documents, and door-to-door transport contracts. In view of that, the Comité Maritime International (CMI) initially prepared a draft Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea. Then, the series of negotiations took place at the United Nations Commission for International Trade Law (UNCITRAL) during 2001–2008 and the result was the adoption of the Rotterdam Rules. On 11 December 2008, the United Nations General Assembly adopted the Rotterdam Rules. These rules establish a uniform and modern legal regime to govern international contracts of carriage wholly or partly by sea and provide legal certainty, new access as well as efficiency of international carriage of goods wholly or partly by sea. These rules further provide legal basis for several commercial and technological developments occurred in maritime transport, i.e., containerisation, the use of electronic transport documents and door-to-door transport contracts. The Rotterdam Rules facilitate a modern alternative to earlier international carriage of goods by sea regimes. Therefore, it is obvious that the Rotterdam Rules can play a crucial role in promoting trade and economic development at both domestic and international level. On 23 September 2009, the Rotterdam Rules were opened for signature in Rotterdam, the Netherlands. It currently has 25 signatories, namely Armenia, Cameroon, Congo, Democratic Republic of the Congo, Denmark, France, Gabon, Ghana, Greece, Guinea, Guinea-Bissau, Luxembourg, Madagascar, Mali, Netherlands, Niger, Nigeria, Norway, Poland, Senegal, Spain, Sweden, Switzerland, Togo and the United States of America. The signatory States will have to replace their carriage of goods by sea regimes with the Rotterdam Rules after ratification and its entry into force. Out of 25 signatories, only four States (i.e., Cameroon, Congo, Spain and Togo) have ratified it as at 15 February 2019. Article 94 of the Rotterdam Rules provides that ‘this Convention enters into force on the first day of the month following the expiration of one year after the date of deposit of the twentieth instrument of ratification, acceptance, approval or accession’. It has, therefore, not yet come into force even after being lapsed for almost a decade. This is mainly because major maritime countries are not much in favour of the Rotterdam Rules which increase the obligation and liability of a carrier in comparison to previous international carriage of goods by sea regimes. Even Spain has been subjected to numerous criticisms made by academics as well as economic sectors. The ratification of the Rotterdam Rules has had negative impact towards Spain which has one of the major maritime transportation industries. Accordingly, this paper aims to analyse critically the extent of the carrier’s obligation as well as its liability as extended under the Rotterdam Rules.